Clock-Frequency Assignment for Multiple Clock Domain Systems-on-a-Chip - Sirowy, Scott; Wu, Yonghui; Lonardi, Stefano; Vahid, Frank (2007 Design, Automation & Test in Europe Conference & Exhibition, 2007)
Modern systems-on-a-chip platforms support multiple clock domains, in which different sub-circuits are driven by different clock signals. Although the frequency of each domain can be customized, the number of unique clock frequencies on a platform is typically limited. We define the clock-frequency assignment problem to be the assignment of frequencies to processing modules, each with an ideal maximum frequency, such that the sum of module processing times is minimized, subject to a limit on the number of unique frequencies. We develop a novel polynomial-time optimal algorithm to solve the problem, based on dynamic programming. We apply the algorithm to the particular context of post-improvement of accelerator-based hardware/software partitioning, and demonstrate 1.5times-4times additional speedups using just three clock domains